An Investigation of Procedural Radiation Dose Level Awareness and Personal Training Experience in Communicating Ionizing Radiation Examinations Benefits and Risks to Patients in Two European Cardiac Centers. Issue 1 (July 2019) - Banerjee, I.; McNulty, J. P.; Catania, D.; Maccagni, D.; Masterson, L.; Portelli, J. L.; Rainford, L.
Abstract : Purpose: Cardiac interventional practitioners need to be appropriately informed regarding radiation dose quantities and risks. Communicating benefit-risk information to patients requires attention as specified in Basic Safety Standards Directive 2013/59/Eurotom. This study investigated the awareness of procedural radiation dose levels and the impact of personal training experience in communicating ionizing radiation benefit-risks to patients. Methodology: A questionnaire, consisting of 28 questions, was distributed directly to adult and pediatric interventional cardiology specialists at specialized cardiovascular imaging centers in Dublin, Ireland and Milan, Italy. Results: A total of 18 interventional cardiologists (senior registrar to consultant grades with between 2 y to over 21 y experience in cardiac imaging) participated. The majority of participants (n = 17) stated that parents of pediatric and adult patients should be informed of the potential benefits and risk. All participants indicated they had radiation safety training; however, 50% had not received training in radiation examination benefit-risk communication. Despite this, 77.8% (n = 14) participants indicated a high confidence level in successfully explaining risks and/or benefits of cardiac imaging procedures. When asked to estimate effective dose (ED) values for common cardiac imaging procedures less than 50% identified appropriate dose ranges. All participants underestimated procedural dose values based on recent European data. 50% (n = 9) participants answered all questions correctly for a number of true or false radiation risk statements. Conclusion: Benefit-risk communication training deficits and inaccurate understanding of radiation dose levels was identified. Further research and training to support clinicians using radiation on a daily basis is required.